Fluorescent Nanodiamond-bacteriophage Conjugates Maintain Host Specificity - Trinh, Jimmy T. (Biotechnol Bioeng, 2018)
Rapid identification of specific bacterial strains within clinical, environmental, and food samples can facilitate the prevention and treatment of disease. Fluorescent nanodiamonds (FNDs) are being developed as biomarkers in biology and medicine, due to their excellent imaging properties, ability to accept surface modifications, and lack of toxicity. Bacteriophages, the viruses of bacteria, can have exquisite specificity for certain hosts. We propose to exploit the properties of FNDs and phages to develop phages conjugated with FNDs as long-lived fluorescent diagnostic reagents. In this study, we develop a simple procedure to create such fluorescent probes by functionalizing the FNDs and phages with streptavidin and biotin, respectively. We find that the FND-phage conjugates retain the favorable characteristics of the individual components and can discern their proper host within a mixture. This technology may be further explored using different phage/bacteria systems, different FND color centers and alternate chemical labeling schemes for additional means of bacterial identification and new single-cell/virus studies.